An investigation on speed measurement method of hermetic compressor based on current fluctuation. (April 2018) - Zhe, Sun; Jiangping, Gu; Huaqiang, Jin; Yuejin, Huang; Xi, Shen
Highlights: Proposed a measurement method based on current signal for hermetic compressor. Given an algorithm for speed-related signal extracted. Explains the reason of why envelope existed and the relationship of current signal and speed value in the mathematics level. Abstract: As an important parameter of hermetic compressor, the speed value has direct effects on the cooling capacity, control performance and power consumption of the refrigeration system. Therefore, modern refrigeration industry has put forward higher requirement for measuring the speed of the compressor. Conventional speed measurement methods are based on shell vibration and discharge pressure fluctuation. However, shell vibration-based methods require more elaborate instrumentation, leading to more complex and expensive procedure, as well as unsatisfied accuracy. Discharge pressure fluctuation-based methods can destruct mechanical structure and influence the state of fluid flow. This paper proposed a measurement method based on slip signal and presented a Hilbert transform-based algorithm to improve the extraction accuracy and real-time measurement, and to reduce the complexity of the measurement system. Compared with the standard measurements generated by the compressor with encode, under the 1 s sampling time, it is possible to reach a maximum error smaller than ± 1 rpm, which can prove broad application prospect in the refrigeration industry. Graphical abstract: Image, graphical abstract